Heat stress effects on substrate oxidation rates during incremental cycling - Maunder, E.; Plews, D. J.; Kilding, A. E. (Sport and Exercise Science New Zealand Conference, 2018, 2018)
Heat stress augments carbohydrate metabolism during prolonged exercise. We sought to determine if this effect is regulated by exercise intensity. In randomised, counterbalanced order, nine endurance-trained male cyclists performed incremental exercise tests (IET) in 18 and 35°C. Physiological variables were compared between-IETs at the absolute workloads eliciting the first ventilatory threshold in 35°C (VT1heat, 184 ± 18 W), first ventilatory threshold in 18°C (VT1temp, 219 ± 40 W), and second ventilatory threshold in 18°C (VT2temp, 266 ± 37 W). Carbohydrate oxidation rate was not significantly different at VT1heat, tended to be elevated by heat stress at VT1temp (2.38 ± 0.80 vs. 2.17 ± 0.70 g.min-1, ES = 0.27 ± 0.31, P = 0.14), and was significantly elevated by heat stress at VT2temp (3.89 ± 1.05 vs. 3.33 ± 0.71 g.min-1, ES = 0.72 ± 0.41, P = 0.02). Heat stress elevated plasma lactate concentration at VT1temp and VT2temp, and significantly elevated rectal and estimated muscle temperatures. The present investigation suggests exercise intensity regulates the heat stress-induced stimulation of carbohydrate oxidation during incremental cycling, with greater effects at higher intensities. These preliminary results have implications for determining the competitions and pacing strategies in which heat stress impacts carbohydrate metabolism.